Persepsi dan Pemahaman Pelaku Usaha Terhadap Pentingnya Laporan Keuangan pada UMKM - Santiago, Mohammad David; Estiningrum, Sri Dwi (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This study aims to see the perceptions and understanding of entrepreneurs of Micro, Small and Medium Enterprises (MSMEs) on the importance of financial reports.